Is TWEAK a Biomarker for Autoimmune/Chronic Inflammatory Diseases? - Bertin, Daniel; Stephan, Delphine; Khrestchatisky, Michel; Desplat-Jégo, Sophie (Frontiers in Immunology, 2013)
The TWEAK/Fn 14 pathway is now well known for its involvement in the modulation of inflammation in various human autoimmune/chronic inflammatory diseases (AICID) including lupus, rheumatoid arthritis and multiple sclerosis. A panel of data is now available concerning TWEAK expression in tissues or biological fluids of patients suffering from AICID, suggesting that it could be a promising biological marker in these diseases. Evidences from several teams support the hypothesis that blocking TWEAK/fn14 pathway is an attractive new therapeutic lead in such diseases and clinical trials with anti-TWEAK blocking antibodies are in progress. In this mini-review we discuss the potential use of TWEAK quantification in AICD management in routine practice and highlight the challenge of standardizing data collection to better estimate the clinical utility of such a biological parameter.